2022
DOI: 10.3390/plants11060771
|View full text |Cite
|
Sign up to set email alerts
|

Horticultural Characteristics of Summer Apple Cultivars from Turkey

Abstract: Early varieties with a short active vegetation period are not exposed to abiotic stress factors for instance drought, high temperature, etc., caused by global climate change, and biotic stress factors such as codling moth (Cydia pomonella) and apple scab (Venturia inequalis) that cause serious economic losses. Therefore, their places are extremely important regarding sustainable, economical and quality production. In this context, four early varieties of apple (‘Vista Bella’, ‘Summer Red’, ‘Williams Pride’ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In this context, a strong positive correlation was determined between fruit weight and fruit width and fruit length respectively at r: 0.75*** and r: 0.80***. The increase in fruit size causes a decrease in the amount of dry matter per unit area by increasing the intercellular space (Mertoğlu et al 2022). For this reason, generally medium-high negative correlations were found between the pomological characteristics and chemical characteristics of the fruits [34].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In this context, a strong positive correlation was determined between fruit weight and fruit width and fruit length respectively at r: 0.75*** and r: 0.80***. The increase in fruit size causes a decrease in the amount of dry matter per unit area by increasing the intercellular space (Mertoğlu et al 2022). For this reason, generally medium-high negative correlations were found between the pomological characteristics and chemical characteristics of the fruits [34].…”
Section: Resultsmentioning
confidence: 85%
“…Firstly, 50% inhibition concentration (IC 50 ) was calculated by drawing percent inhibition against the sample concentrations. Then, up to IC 50 value samples were taken and the ability to remove DPPH radicals was determined according to the method speci ed by Mertoğlu et al (2022). Results were expressed as a percentage (%) in which ascorbic acid used as a positive control.…”
Section: Spectrophotometric Assaysmentioning
confidence: 99%
“…As a defense mechanism against the harmful effects of high UV rays, plants produce phenolic compounds with high UV absorbing ability in epidermal tissues, in the phenylpropanoid pathway [ 37 ]. Josuttis et al [ 38 ] reported that the quantity of phenolic acids in strawberries grown in open field were determined higher than those cultivated inside UV-blocking plastic tunnels because of exposed to higher UV that is increased at high altitudes [ 29 ]. At higher altitudes, the light intensity and the temperature difference between day and night increase.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a strong positive correlation was found between fruit weight and fruit width and also between fruit weight and fruit length respectively at ( r = 0.75*** and r = 0.80***). The increase in fruit size causes a decrease in the dry matter per unit area due to an increase in the intercellular space [ 29 ]. Therefore, medium-to-high negative correlations were found between the pomological characteristics and chemical characteristics of fruits [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation